A complex grid investment decision method considering source-grid-load-storage integration - Zhang, Zheliang; Xia, Pei; Zhang, Xiaoxing (Frontiers in Energy Research, 2023)
With the widespread use of renewable energy worldwide, the impact of its randomness and volatility on the grid is increasing. To promote the consumption of renewable energy, the traditional grid is being transformed into a complex grid with integrated source–grid–load–storage. Since the complex grid has the characteristics of source–grid–load–storage interaction, the traditional grid investment decision method will no longer be applicable. First, this study proposes the unilateral indexes of source, grid, load, and storage in complex grids and the interactive indexes considering grid–source interaction, load–grid interaction, source–load interaction, source–storage interaction, load–storage interaction, and grid–storage interaction are proposed to establish the investment decision system. Then, a hesitance fuzzy linguistic term set combined with regret theory is used to calculate the specific values of the subjectivity index, taking into full consideration the regret avoidance and loss avoidance psychology of investors. In order to comprehensively consider the index preference of investors and the objectivity of weight assignment, a combined weighting method based on the analytic network process (ANP) and entropy weight method (EWM) is obtained according to the game theory method. Finally, using a grid in a region of southwest China as an example, the results demonstrate that the construction order obtained in this study can prioritize the projects with the largest comprehensive benefits while considering the subjective preferences of decision-makers and the objectivity of the indexes.